(untitled) (Philological Studies, 2019)
Patriarchy has created an evaluation system which keeps generating interpersonal relations and society systems based on discrimination. The core of the problem is disharmony between the female and male principle. The terms “man” and “woman” weren’t built on experience of a deeper insight in the divine creation in which both principles are in harmony, intertwining and fusing on a higher level, but, rather on the construction of prejudice and projections. Feminism shouldn’t be understood only as a strive for liberation of the woman, but, also for liberation of man to access a higher status. The moral qualities such as care, unity, cooperation, solidarity, growth, risе, nourishment, protection, shelter, weave the new tissue of the texture in the relationships which are gaining larger and larger meaning. The acceptance of the ethics of care and the motherly ethic is a way to transform society, as well as to “release” nature of the merciless exploitation, so that it can let planet Earth transform into an agreeable place for living of the contemporary and the following generations.